Effect of sodium thiazolinyl dithiopropane sulphonate (SH110) addition on electroplating nanotwinned copper films and their filling performance of fine-pitch redistributed layer (RDL). (1st January 2023) - Huang, Jing; Gao, Li-Yin; Peng, Zhen-Jia; Li, Zhe; Liu, Zhi-Quan; Sun, Rong
Abstract: Nanotwinned copper is a potential microelectronic interconnection material due to its superior strength and conductivity, however, its filling ability is urgently needed to improve before its application in the field of advanced packaging. The effect of additive (sodium thiazolinyl dithiopropane sulphonate, SH110) addition on the surface roughness, microstructure, mechanical properties and filling capacity of nanotwinned copper films was investigated. The surface roughness and grain size were firstly reduced then increased with the increasing concentrations of SH110, reaching the minimum value at 10 ppm. It was noticed that copper films with 10 ppm SH110 also possessed superior tensile strength and elongation, which were measured as 481 MPa and 3.68% on average of 12 μ m thick samples by dynamic thermo-mechanical analyzer. Further, their uniformity and flatness of redistributed layers (RDLs) were controlled as 2% and 1.9%, which were significantly improved compared to the samples without SH110 (7.6% and 4.7%). As demonstrated by linear sweep voltammetry analysis and galvanostatic measurement, the SH110 could cooperate well with gelatin and serve as a combination of accelerator and leveler, resulting in the improvement of filling capacity for nanotwinned copper RDLs.